The Effect of E-Tax System and Tax Socialization on Taxpayer Compliance During Pandemic and Endemic - Tiara; Wahyuni, Putri (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
The purpose of this study is to determine whether E-Tax System and Tax Socialization have significant effect on Taxpayer Compliance During Pandemic and Endemic at PT. Kurniaputra Mandiri. This study uses quantitative data methods, and the data source is primary data. The population in this study are all permanent employees who work at PT Kurniaputra Mandiri. The sample in this study are permanent employees that have Tax Identification Number (NPWP) who work at PT Kurniaputra Mandiri in total of 30 respondents using purposive sampling methods. Data analysis and testing consist of validity test, reliability test, descriptive statistics, the classical assumption test, multiple regression analysis, partial hypothesis testing (T test), and simultaneous hypothesis testing (F test), and coefficient of determination test. The results of this study indicate that E-Tax System doesn’t have significant effect on Taxpayer Compliance with a T count of 0,499 < T table 2,048. Tax Socialization has a partially significant effect on Taxpayer Compliance with a T count of 2,964 > T table 2,048. E-Tax System and Tax Socialization simultaneously have a significant effect on Taxpayer Compliance with a F count of 20,019 > F table 3,35 and regression coefficient value of 59,7%.